KONSEP BISNIS ISLAMI: TUJUAN, KARAKTERISTIK DAN PRINSIP - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to determine the goals, principles and characteristics of business practices. The research method is a qualitative type of library study. The results of the research are that the goal of Islamic business is to hope for the pleasure of Allah SWT; Profit Target (Result); Growth and Sustainability; and Business Blessings. The characteristics of Islamic business are that it has divine elements; Systematic: Comprehensive (Syumuliyya); Universal; Mashlahah; Worldly and Ukrainian. Other Sharia business characteristics are: Rabbaniyah (monasticism); Akhlaqiyyah (morals & behavior); Insaniyyah (humanity); Washathiyyah (moderation/balance). The character of sharia business has several aspects, namely: Based on Islamic values; Material and spiritual aspects (worldly & spiritual); Halal orientation; Usefulness, blessings, & benefits; and Social responsibility. Islamic business has the basic principles of Islamic business ethics including: The principle of monotheism; Principles of Science; Principles of Justice; Principle of Responsibility; Principle of Freedom; Principle of Virtue (Ihsan); and Halal vs Haram Principles.